MANUFACTURING DEFECTS BASED ON ARTICLE 1367 OF THE INDONESIAN CIVIL CODE - Royani, Esti; Sarikun; Zahra, Shafirah Fitria (Proceeding of International Conference on Multidisciplinary Research, 2024)
Legal Liability arises as a result of an Agreement or Contract which originates from an action that can cause harm to another person because it is done wrongly. Buying and Selling is an agreement or agreement or contract where one party binds himself to hand over an object to another party who binds it. himself to pay the price that has been promised, from the ongoing buying and selling, it is not uncommon for us to encounter goods with production defects. The problem in this research is what is the form of legal responsibility for buying and selling dimsum with production defects based on Article 1367 of the Civil Code towards the buyer the disadvantaged and How can consumers demand legal responsibility for buying and selling dimsum with production defects based on Article 1367 of the Civil Code. The type of research used is normative legal research. The research results show that basically there is a relationship between business actors and buyers, the relationship in question is the rights and obligations between business actors and buyers, therefore consumer protection law regulates the rights and obligations of business actors and consumers. whose fulfillment is guaranteed through law enforcement. The conclusion of this research is that the obligations of business actors are the responsibilities that must be carried out by business actors towards buyers and conversely, consumer rights are the obligations of buyers to business actors. The advice from this research is that business actors should pay attention to even the smallest things so that things that harm other people do not happen.